Implementation Of Bsi Griya Hasanah Financing With Academic Murabahah Fatwa Dsn MUI Perspective In Indonesian Sharia Bank Sumenep Trunojoyo Subsidiary Branch Office 1: Akad Murabahah - mutmainnah mutmainnah; Cici’ Insiyah (Cita konsultindo, 2023)
Bank Syariah Indonesia (BSI) Sumenep Trunojoyo 1 is one of the Islamic banks that adopt Murabahah financing with the principle of buying and selling provided by the bank for customers, such as the BSI Griya Hasanah financing product. Provisions related to Murabahah contracts in Islamic banks have been regulated in the DSN-MUI Fatwa so that they are by sharia principles, but in practice, there are still several banks that have not implemented Murabahah contracts perfectly. This research was raised from the problems described in 2 research focuses, namely: 1. How is the implementation of BSI griya hasanah financing with a Murabahah contract from the perspective of DSN-MUI Fatwa at BSI KCP Sumenep Trunojoyo 1. 2. What are the obstacles faced in BSI financing griya hasanah at BSI KCP Sumenep Trunojoyo 1. The method used in this research is using a descriptive qualitative approach with a case study type. The object studied was BSI Sumenep Trunojoyo 1. The data collection process was carried out through observation, interviews, and documentation. To analyze the data, researchers used data reduction, data presentation, and conclusion. Meanwhile, to check the validity of the data, researchers used technical triangulation. From the results of this study, it is known that the implementation of BSI griya hasanah financing with a Murabahah contract is by DSN MUI Fatwa No 04/DSN-MUI/IV/2000. This can be seen from the mechanism used by BSI KCP Sumenep Trunojoyo 1 for BSI griya hasanah financing products. In this financing, a Murabahah contract occurs after the bank has proof of house ownership in the form of a certificate. Where the purchase of the house is represented to the customer on behalf of the bank, after the house certificate is submitted to the bank, then the bank declares the principal price and margin to the customer, after the customer and the bank agree on a specified price, then proceeds to the implementation of the Murabahah contract. ah for financing BSI griya hasanah. As for the guarantee used in this financing, the bank sets a guarantee in the form of a certificate of the house that has been purchased.